2019
DOI: 10.1161/circulationaha.118.036336
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of S-Adenosylhomocysteine Hydrolase Induces Endothelial Dysfunction via Epigenetic Regulation of p66shc-Mediated Oxidative Stress Pathway

Abstract: Background: Elevated levels of S-adenosylhomocysteine (SAH), the precursor of homocysteine, are positively associated with the risk of cardiovascular disease and with the development and progression of atherosclerosis. However, the role of SAH in endothelial dysfunction is unclear. Methods: Apolipoprotein E–deficient ( apoE −/ − ) mice received dietary supplementation with the SAH hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 46 publications
4
44
0
1
Order By: Relevance
“…Overall, the analysis showed the evolutionary relationship among the species. It is also meant that the protein plays a crucial role in the regulation of abiotic and biotic stress response in plants [37] and regulates oxidative stress in animals [32], which is confirming the clustering pattern due to their function that is involved in stress mechanism.…”
Section: Apahc Homology Search and Its Phylogenysupporting
confidence: 67%
See 1 more Smart Citation
“…Overall, the analysis showed the evolutionary relationship among the species. It is also meant that the protein plays a crucial role in the regulation of abiotic and biotic stress response in plants [37] and regulates oxidative stress in animals [32], which is confirming the clustering pattern due to their function that is involved in stress mechanism.…”
Section: Apahc Homology Search and Its Phylogenysupporting
confidence: 67%
“…The homocysteine precursor present in the AHc is strongly correlated with cardiovascular disease and growth of atherosclerosis [31]. However, recently reported that AHc also helps in regulating oxidative stress level in patients suffering from coronary artery diseases and also prevents endothelial dysfunction [32]. Also, deficiency of AHc promotes oxidative stress by decreasing Na + , K + -ATPase activity in cerebral cortex of rats by increasing S-adenosylmethionine [33].…”
Section: Analysis Of Apahc Whole Sequencementioning
confidence: 99%
“…In another study, plasma concentration of SAH, but not of Hcy, was strongly associated with traditional CVD risk factors and subclinical atherosclerosis in subjects at low CVD risk [15]. Moreover, plasma SAH was found to be inversely associated with a measure of endothelial dysfunction (namely, endothelial nitric oxide synthase-dependent vasodilation) in a small sample of patients with coronary artery disease [16].…”
Section: Introductionmentioning
confidence: 94%
“…The introduction of an internal standard made it possible to improve the CE reproducibility by reducing the CV of between‐run reproducibility from 6–10% to 2–3% and decreasing intraday precision from 4–6% to 1.5–3.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, an increase in the level of SAH or a decrease in the SAM/SAH ratio is considered to be an independent marker of a number of cardiovascular diseases . A key role of these metabolites, primarily SAH, in the development of endothelial dysfunction (the leading pathogenic process of most vascular diseases) was confirmed in experimental studies .…”
Section: Introductionmentioning
confidence: 99%